Religious Well-Being and Suicide Ideation in Gunungkidul: Exploring the Pulung Gantung Phenomenon among Javanese Communities - Fredyarini Soedjiwo, Novena Ade; Entas, Derinta; Suroyo, Suroyo; Putra, Bima Maulana; Guidi, Elisa; Karimi, Amir (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
The phenomenon of suicide in the context of the Pulung Gantung myth has become a serious concern. However, research that specifically examines the relationship between religious well-being and suicidal ideation in the context of Javanese culture, particularly in areas with a high prevalence of suicide, such as Gunungkidul, is still minimal. The present study aims to identify the role of the Pulung Gantung myth in mediating the relationship between religious well-being and suicidal ideation. A qualitative approach with a case study design was employed to explore the unique experiences of Javanese people in Gunungkidul. Snowball sampling was used to identify key informants who met specific criteria, and semi-structured interviews were conducted to collect data on religious well-being and suicidal ideation. To ensure the accuracy and avoid any offence, all collected data underwent a meticulous verbatim analysis. The Pulung Gantung myth exerts a substantial influence on the incidence of suicidal ideation within the Javanese community of Gunungkidul. This myth has the capacity to intensify feelings of despair, thereby expediting the process of arriving at the decision to take one's own life. The development of programs that promote community participation in religious activities. The implications of this study suggest a necessity to reinterpret the meaning of the Pulung Gantung myth so that it is no longer directly associated with suicide.